2019
DOI: 10.3390/catal9110965
|View full text |Cite
|
Sign up to set email alerts
|

Assessment of Degradation Behavior for Acetylsalicylic Acid Using a Plasma in Liquid Process

Abstract: Acetylsalicylic acid (ASA) is a pharmacologically active compound. In this study, ASA was decomposed effectively using a plasma in liquid phase process with hydrogen peroxide and TiO2 photocatalyst. Increasing the electrical power conditions (frequency, applied voltage, and pulse width) promoted plasma generation, which increased the rate of ASA decomposition. The added hydrogen peroxide increased the rate of ASA degradation, but injecting an excess decreased the degradation rate due to a scavenger effect. Alt… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
3
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 32 publications
0
3
0
Order By: Relevance
“…The GS-MS results indicated that the methylparaben was completely decomposed to a certain extent, with carbon dioxide and water as the presumed end products. The decomposition presumably takes place here due to the highly reactive environment and the strong radical formation (Cui et al 2018, Abramov et al 2021, Bang et al 2019. However, even with the longest treatment period, elimination was not even close to 100%.…”
Section: Discussionmentioning
confidence: 95%
See 1 more Smart Citation
“…The GS-MS results indicated that the methylparaben was completely decomposed to a certain extent, with carbon dioxide and water as the presumed end products. The decomposition presumably takes place here due to the highly reactive environment and the strong radical formation (Cui et al 2018, Abramov et al 2021, Bang et al 2019. However, even with the longest treatment period, elimination was not even close to 100%.…”
Section: Discussionmentioning
confidence: 95%
“…13.3 kWh, the price of a single cycle treatment would be over 1 €/m3 (Considering the average electricity price of 0.3263 €/kWh in Germany in 2021 (Umwelt Bundesamt 2021)), however, parts of the consumption are also due to external pumps and here lies a potential for cost savings. The use of oxidizing agents, such as hydrogen peroxide, would also be conceivable (Bang et al 2019), to heighten the efficiency and reduce the number of cycles needed. An extension of the monitoring equipment for an actual industrial plant would also make sense in order to be able to ensure a constant plasma intensity.…”
Section: Figure 6 Comparison Of the Peaks After Gas Chromatography Wi...mentioning
confidence: 99%
“…Moreover, it was observed that the increase of the number or size of the pores enhances both the volume and surface discharges. The addition of a heterogeneous TiO 2 -based catalyst can be efficient in the degradation of pharmaceutical compounds present in aqueous solution such as acetylsalicytic acid [10]. Furthermore, the addition of hydrogen peroxide increased the rate of acetylsalicytic acid degradation, but injecting an excess decreased the degradation rate due to a scavenger effect.…”
mentioning
confidence: 99%